2020
DOI: 10.1108/apjba-10-2019-0210
|View full text |Cite
|
Sign up to set email alerts
|

Organizational virtuousness, subjective well-being, and job performance

Abstract: PurposePast research has convincingly shown that higher employee subjective well-being, or happiness, is a source of higher job performance and retention. This paper therefore examines the relationships between organizational virtuousness, subjective well-being, and individual job performance among French and Japanese employees.Design/methodology/approachA questionnaire survey was conducted among Japanese and French managers and staff at Japanese and French domestic companies and structural equation modeling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 60 publications
1
26
0
2
Order By: Relevance
“…Further, improved work-life balance because of these resources may have led to a reduction in work exhaustion for an individual like previous research reported that autonomy that comes with telecommuting helps in mitigating workload pressure, exhaustion and further the negative impacts (Sardeshmukh et al , 2012; Allen et al , 2015; Gajendran et al , 2015; Vander Elst et al , 2017). As recent studies also found that, telecommuting improves well-being when the work arrangement is employee-centric (Sánchez, 2017; Avgoustaki and Frankort, 2018) and this also helps the organization in the long run because improved well-being increases performance and productivity and employees are less likely to quit (Magnier-Watanabe et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Further, improved work-life balance because of these resources may have led to a reduction in work exhaustion for an individual like previous research reported that autonomy that comes with telecommuting helps in mitigating workload pressure, exhaustion and further the negative impacts (Sardeshmukh et al , 2012; Allen et al , 2015; Gajendran et al , 2015; Vander Elst et al , 2017). As recent studies also found that, telecommuting improves well-being when the work arrangement is employee-centric (Sánchez, 2017; Avgoustaki and Frankort, 2018) and this also helps the organization in the long run because improved well-being increases performance and productivity and employees are less likely to quit (Magnier-Watanabe et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that employees experience high and improved emotions/positive affect if they feel that the organizations where they work are caring and trustworthy. Along with this, the organizational environment accompanied by integrity and forgiveness also enhances employees' happiness (Magnier-Watanabe et al, 2020). Thus, based on the favorable association between organizational virtuousness and different well-being dimensions (Ahmed et al, 2018;Magnier-Watanabe et al, 2020), it can be ascertained that organizational virtuousness influences employees' positive effect favorably, thus we hypothesized that Hypothesis 1: Organizational virtuousness is favorably associated with positive affect…”
Section: Organizational Virtuousness and Positive Affectmentioning
confidence: 94%
“…Further, the change in the scenario whereby the employees are not only keen to have financial benefits (Chadha, 2018) but also require support, and an optimal environment to feel full-fledged and motivated, mandates to pay attention to organizational virtuousness. Notably, organizational virtuousness is favorably associated with different well-being dimensions like psychological (Magnier-Watanabe et al, 2020) and affective well-being (Ahmed et al, 2018). Generally, organizational virtuousness refers to "the transcendent, elevating behavior of the organization's members" comprising of five sub-dimensions (Cameron et al, 2004).…”
Section: Organizational Virtuousness and Positive Affectmentioning
confidence: 99%
“…A poor employee's well-being perceptions adversely affect on-job service performance (Anderson and Ostrom, 2015). On the other side, positive perceptions of well-being enhance work performances (Magnier-Watanabe et al, 2020). The psychological well-being of employees is a core agenda among human resource policymakers and researchers (Guest, 2017).…”
Section: Introductionmentioning
confidence: 99%